Terapi Bermain : Mewarnai Dengan Tingkat Kooperatif Anak Prasekolah Akibat Hospitalisasi : Literature Review - Achmad Latip (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Introduction : Coloring is a skill to give color with various media. Coloring is an intervention that can suppress anxiety, stress, and uncooperative attitudes in children. In coloring activities, children are given the opportunity to express, increase creativity, train self-confidence and fine motor skills. Objective: To compare research articles and journals whether coloring therapy has an effect on the cooperative level of preschool children due to hospitalization. Methods: This literature review uses a literature review design, a systematic, explicit and reproducible method for identifying, evaluating and synthesizing research works and ideas that have been produced by researchers and practitioners. The literature review aims to analyze and synthesize existing knowledge related to the topic to be studied to find empty space for research to be carried out. Results: Of the 20 journals analyzed, almost all of them showed that coloring therapy can suppress uncooperative attitudes in preschool children due to hospitalization. Suggestion: Using coloring therapy as an action in increasing the level of cooperation in preschool children due to hospitalization.